The Effectiveness of Spiritual-Based Relaxation Technique on Patients With Post-Traumatic Stress Disorder After Treatment in an Integrated Cardiac Intensive Care Unit - Diah Priyantini; Suyatno Hadi Saputro; Siswanto Agung Wijaya; Daviq Ayatulloh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Patients who have undergone treatment in an Integrated Cardiac Intensive Care Unit may experience psychological distress after discharge, including symptoms of post-traumatic stress disorder. Exposure to life-threatening cardiac events, invasive procedures, uncertainty, and the intensive care environment may contribute to persistent fear, intrusive memories, sleep disturbance, and emotional dysregulation. Spiritual-based relaxation technique, including Spiritual Emotional Freedom Technique, combines relaxation, spiritual affirmation, acceptance, and body-based stimulation to reduce emotional distress. Objective: This study aimed to examine the effectiveness of a spiritual-based relaxation technique in reducing post-traumatic stress disorder symptoms among patients after treatment in an Integrated Cardiac Intensive Care Unit. Methods: A pre-experimental one-group pretest–posttest study was conducted among 30 patients who had completed treatment in an Integrated Cardiac Intensive Care Unit. Participants were selected using purposive sampling. The intervention consisted of spiritual-based relaxation sessions delivered over three consecutive days. Post-traumatic stress disorder symptoms were measured before and after the intervention using a standardized PTSD symptom questionnaire. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Results: The mean age of participants was 56.4 years, and most participants were male. The mean PTSD symptom score decreased from 42.6 ± 7.8 before the intervention to 28.9 ± 8.1 after the intervention. The median PTSD score decreased from 43.0 to 29.0. The Wilcoxon signed-rank test showed a statistically significant reduction in PTSD symptoms after the intervention (Z = −4.62, p < .001). The mean score reduction was 13.7 points, indicating clinically meaningful improvement after spiritual-based relaxation. Conclusion: Spiritual-based relaxation technique was effective in reducing PTSD symptoms among patients after treatment in an Integrated Cardiac Intensive Care Unit. This intervention may be considered as a simple, low-cost, and holistic nursing approach to support psychological recovery after intensive cardiac care. Further studies using randomized controlled designs and larger samples are recommended.